2019
DOI: 10.1002/slct.201900361
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ Infrared Study of CO2 Hydrogenation to Formic Acid by Using Rhodium Supported on Titanate Nanotubes as Catalysts

Abstract: Titanate nanotubes (TiNT) were synthesized by hydrothermal method and used as support of rhodium nanoparticles. Results of X-Ray diffraction (XRD) and Raman spectroscopy of TiNT revealed its structure of Na 2 Ti 3 O 7 , while the results of Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and physisorption of N 2 confirmed the multilayer nanotubular morphology with external diameter of ∼ 12 nm, length > 100 nm and a BET surface area of 195 m 2 g À 1 . The TEM analysis of the rhodium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 72 publications
(131 reference statements)
0
29
0
Order By: Relevance
“…It was proposed that the Na + content in TiNT plays an important role in the various carbonate formation processes. The reduced Rh/TiNT has the ability to form rhodium hydride complexes which can interact with bidentate carbonates to yield formate species and facilitates the further hydrogenation to formic acid [44]. This proposal was supported by the infrared spectroscopic results on Rh/MgO.…”
Section: Reaction Of Co 2 With H 2 On Titania-supported Rh Catalystsmentioning
confidence: 80%
See 2 more Smart Citations
“…It was proposed that the Na + content in TiNT plays an important role in the various carbonate formation processes. The reduced Rh/TiNT has the ability to form rhodium hydride complexes which can interact with bidentate carbonates to yield formate species and facilitates the further hydrogenation to formic acid [44]. This proposal was supported by the infrared spectroscopic results on Rh/MgO.…”
Section: Reaction Of Co 2 With H 2 On Titania-supported Rh Catalystsmentioning
confidence: 80%
“…The CO 2 dissociation occurs on Rh/TiNT (titanate nanotube) and Rh/TiNW (titanate nanowire) at 493 K but at smaller extent than on Rh/TiO 2 under the same experimental conditions [43]. Other authors found that the CO 2 dissociation at room temperature does not occur; CO band was not detected on Rh/TiNT [44].…”
Section: Adsorption and Dissociation Of Co 2 On Rh And On Supported Rmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the absorption band of the C=O group of formaldehyde adsorbed on Rh/TiO2 appears at lower wavenumbers, at about 1727 cm −1 , and it forms at higher temperatures [109]. Although the vibration frequency of C=O groups in The bands detected between 1550-1570 cm −1 and 1379 cm −1 could be assigned to the asymmetric and symmetric vibration of the OCO group of formate species, respectively [94,[102][103][104][105][106][107]. The absorption found at about 1620 cm −1 could be attributed to water formed in the reaction.…”
Section: Co 2 Hydrogenation On Titania and Titanate Supported Rhmentioning
confidence: 95%
“…The hydrogenation of CO 2 was studied extensively on titania (TiO 2 ) supported Rh [20][21][22][23][24][91][92][93] and the reaction was also investigated on titanate (TiONW and TiONT)-supported Rh recently [62,90,94]. In all cases, the supported Rh showed an excellent catalytic activity.…”
Section: Co 2 Hydrogenation On Titania and Titanate Supported Rhmentioning
confidence: 99%